Disparities Criminal Case Against Judge's Decision In Crime Of Narcotics Abuse Viewed From The Purpose Of Criminal Law - Defry Dwi Irmawan; Anis Mashdurohatun (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Criminalization of the criminal case of narcotics abuse by the judges are very diverse. The aim of research to find out and analyze why the disparity in the criminal verdict against narcotics abuse criminal case, how the implementation of the basic objective of sentencing disparity in the criminal verdict against narcotics abuse criminal case. Methods are juridical sociological approach using primary data from interviews with relevant parties associated secondary data of materials applicable laws or regulations. The results of the study, 1) criminal disparity in criminal narcotics abuse, cause by the impact of the crime of narcotics abuses, committing criminal background narcotic abuse, the persuasive principle of Presedent, The existence of freedom and independence of the judge in the 1945 Constitution, the laws existing judicial power, the theory of dissenting opinions, and the doctrine of res judicate hebetur pro veritate. 2) Implementation of the objective of sentencing in criminal disparity criminal case of narcotics abuse, contained in the formulation of a special minimum punishment in Act No. 35 of 2009, is to meet the demands of society and the effectiveness of the influence of general prevention. of punishment meted out, the final attempt of criminal law and serves as a special precaution, prevention against the perpetrators to obtain deterrence and rehabilitation for himself.Keywords: Narcotics abuse; Criminal Disparities; Objective Punishment.